Design, synthesis, biological evaluation, common feature pharmacophore model and molecular dynamics simulation studies of ethyl 4-(phenoxymethyl)-2-phenylthiazole-5-carboxylate as Src homology-2 domain containing protein tyrosine phosphatase-2 (SHP2) inhibitors. Issue 4 (4th March 2021) - Wu, Jingwei; Li, Weiya; Zheng, Zhihui; Lu, Xinhua; Zhang, Huan; Ma, Ying; Wang, Runling
Abstract: SHP2 is a non-receptor protein tyrosine phosphatase (PTP) encoded by the PTPN11 gene involved in cell death pathway (PD-1/PD-L1) and cell growth and differentiation pathway (MAPK). Moreover, mutations in SHP2 have been implicated in Leopard syndrome (LS), Noonan syndrome (NS), juvenile myelomonocytic leukemia (JMML) and several types of cancer and solid tumors. Thus, SHP2 inhibitors are much needed reagents for evaluation of SHP2 as a therapeutic target. A series of novel ethyl 4-(phenoxymethyl)-2-phenylthiazole-5-carboxylate derivatives were designed and synthesized, and their SHP2 inhibitory activities (IC50 ) were determined. Among the desired compounds, 1d shares the highest inhibitory activity (IC50 = 0.99 μM) against SHP2. Additionally, a common feature pharmacophore model was established to explain the structure activity relationship of the desired compounds. Finally, molecular dynamics simulation was carried out to explore the most likely binding mode of compound 1d with SHP2. In brief, the findings reported here may at least provide a new strategy or useful insights in discovering novel effective SHP2 inhibitors. Communicated by Ramaswamy H. Sarma